Managing a Specialty Service During the COVID-19 Crisis: Lessons From a New York City Health System. (October 2020) - Ammar, Adam; Stock, Ariel D.; Holland, Ryan; Gelfand, Yaroslav; Altschul, David
Abstract : The COVID-19 pandemic has stretched health care resources to a point of crisis throughout the world. To answer the call for care, health care workers in a diverse range of specialties are being retasked to care for patients with COVID-19. Consequently, specialty services have had to adapt to decreased staff available for coverage coupled with a need to remain available for specialty-specific emergencies, which now require a dynamic definition. In this Invited Commentary, the authors describe their experiences and share lessons learned regarding triage of patients, staff safety, workforce management, and the psychological impact as they have adapted to a new reality in the Department of Neurosurgery at Montefiore Medical Center, a COVID-19 hot spot in New York City.